Evaluating Axial Strength of Cold-formed C-Section Steel Columns Filled with Green High-performance Concrete - Jasim, Al Mashhadani D. A.; Wong, Leong Sing; Al-Zand, Ahmed W.; Kong, Sih Ying (Civil Engineering Journal, 2024)
Concrete-filled steel tube (CFST) columns that experience outward local buckling under high axial stress remain a significant concern, particularly when thin steel sections are used, as opposed to semi-compact and compact sections. This study investigated the performance of column systems by comparing single- and double-C-section configurations with both hollow and concrete-filled designs. Two types of infill materials were investigated: normal concrete and recycled material concrete, which included 10% waste glass powder as a cement replacement, 8% black high-density polyethylene beads as a sand substitute, and 10% pumice stone as coarse aggregate. To enhance the strength of the proposed CFS column, steel strips and screws were used to connect the flanges of the C-sections. Nine columns were tested experimentally under static axial load. Additionally, finite element analysis software was used to model and evaluate the effects of parameters beyond those investigated in the tests. The results indicated that the load capacity of the double face-to-face section was approximately 3% higher than that of the double back-to-back section. The addition of steel strips, used to connect the lips of the C-section flanges, enhanced the axial strength of the column by approximately 2% compared with the unstrengthened corresponding specimen and delayed buckling in the most vulnerable areas. Furthermore, the recycled infill concrete material had a minimal impact on the axial performance of the analyzed CFS columns compared to the control concrete, with a difference of less than 2.2%. The findings confirm that recycled waste material concrete can achieve performance comparable to that of the conventional concrete. Doi: 10.28991/CEJ-SP2024-010-014 Full Text: PDF